The Effect of Inhalation Aromatherapy on the Anxiety of Hemodialysis Patients at RSU Imelda Pekerja Indonesia Medan in 2023 - Dame, Arta Marisi; Siregar, Muhammad Hamid (Jurnal Kesehatan, Rekam Medis dan Farmasi (JUK-Medifa), 2023)
According to KDIGO (2012) people with chronic kidney disease need hemodialysis therapy. Hemodialysis is the process of exchanging solutes and waste products of the body. The waste substances that accumulate in chronic kidney disease patients are withdrawn by the passive diffusion mechanism of semipermeable membranes. From the results of the analysis that has been carried out at RSU Imelda Pekerja Indonesia on patients undergoing hemodialysis, it was found that 7 out of 22 people undergoing hemodialysis experienced anxiety when they were about to start the hemodialysis process with signs of feeling tense, heart palpitations, nausea and anxiety about side effects during the hemodialysis process. One non-pharmacological therapy is complementary therapy that can be used to reduce some of the complications of hemodialysis such as anxiety, fatigue, pain, sleep quality, stress, and headaches, namely aromatherapy. The purpose of the study was to determine the effect of inhalation aromatherapy on the anxiety of patients undergoing iohemodialysisodi at RSU Imelda Pekerja Indonesia Medan in 2023. This study used quantitative methods. This type of study is pre-experimental with a one-group pretest-posttest design. The study population was 104 people, the study sample was 43 with purposive sampling. Bivariate test with wicoxon test. The results of the study The anxiety level of hemodialysis patients before giving aromatherapy had a mild anxiety level (40-59) as many as 21 people (48.8%), followed by hemodialysis patients with moderate anxiety levels (60-74) as many as 16 people (37.2%), followed by severe anxiety (75-80) as many as 6 people (14.0%). The anxiety level of hemodialysis patients after aromatherapy administration had mild anxiety levels (40-59) as many as 22 people (51.2%), followed by hemodialysis patients with moderate anxiety levels (60-74) as many as 13 people (30.2%), followed by no anxiety (20-39) as many as 5 people (11.6%) and severe anxiety (75-80) as many as 3 people (7.0%). The results of the Wilcoxon test, it was found that there was an effect of inhalation aromatherapy with a decrease in anxiety in hemodialysis patients with sig values. 0.000<0.05.